A Rapid and Convenient Approach to Construct Porous Collagen Membranes via Bioskiving and Sonication-Feasible for Mineralization to Induce Bone Regeneration - Wu, Zhenzhen; Zhong, Juan; Yu, Yingjie; Rong, Mingdeng; Yang, Tao (Frontiers in Bioengineering and Biotechnology, 2021)
Porous mineralized collagen membranes efficiently promote bone regeneration. To generate them, we need to fabricate collagen membranes that are porous. However, the current fabrication method is primarily based on a bottom-up strategy, with certain limitations, such as a long manufacturing process, collagen denaturation, and a failure to control fibril orientation. Using a top-down approach, we explore a novel method for constructing porous collagen membranes via the combined application of bioskiving and sonication. Numerous collagen membranes with well-aligned fibril structures were rapidly fabricated by bioskiving and then sonicated at 30, 60, 90, and 120 W for 20 min. This treatment allowed us to study the effect of power intensity on the physicochemical traits of collagen membranes. Subsequently, the prepared collagen membranes were immersed in amorphous calcium phosphate to evaluate the feasibility of mineralization. Additionally, the bioactivities of the membranes were assessed using preosteoblast cells. Tuning the power intensity was shown to modulate fibril orientation, and the porous membrane without denatured collagen could be obtained by a 20 min sonication treatment at 90 W. The prepared collagen membrane could also be further mineralized to enhance osteogenesis. Overall, this study offers a rapid and convenient approach for fabricating porous collagen membranes via bioskiving and sonication.